THE INFLUENCE OF THE FAMILY ENVIRONMENT AND SELFEFFICACY ON THE INTEREST IN BECOMING A STUDENT TEACHER OF THE EDUCATION STUDY PROGRAM, FACULTY OF ECONOMICS, STATE UNIVERSITY OF JAKARTA 2018 - JPEPA, Admin (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of family environment and selfefficacy on the interest in becoming a teacher for students of theEducation Study Program, Faculty of Economics, State University ofJakarta batch 2018. This research was conducted for 8 monthsstarting from January 2022 to August 2022. The method used in thisstudy is the method survey. Technique uses Proportional StratifiedRandom Sampling with a sample of 175 respondents was obtainedfrom the 2018 Faculty of Economics Education Study Programstudents. The data was collected through distributing questionnairesusing a Likert scale. Based on the results of the research conducted, itwas found that Family Environment has a positive and significanteffect on Interest in Becoming a Teacher. Self-Efficacy has a positiveand significant effect on Interest in Becoming a Teacher. According tothe research hypothesis.